The Effect of Digital Transformation, Tax Policy, Company Characteristics and Perceptions on The Effectiveness of The Tax System During The Covid-19 Pandemic, Moderated By Tax Outreach - Fernanda Meita; Melinda Malau (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to analyze whether digital transformation, tax policy, company characteristics and perceptions of weaknesses in the tax system have an influence on business entity tax compliance and whether tax socialization will strengthen the relationship between the independent variables and the dependent variable. The method used in this research is a causal study. This research was conducted on every Business Entity or every individual involved in tax administration in business entities. The data used is primary data and the data collection technique used is a questionnaire. Pre-pandemic results of tax policy have a positive effect on tax compliance and tax socialization can strengthen the relationship between tax policy and business entity taxpayer compliance. Results during the digital transformation pandemic, tax policy. The perception of the effectiveness of the tax system has a positive effect on tax compliance and tax socialization can strengthen the relationship between tax policy and business entity taxpayer compliance. The implication of this research is that if the socialization of taxation is not carried out clearly and routinely, the tax obligations carried out by business entities will not run well, it will affect the compliance of business entity taxpayers in carrying out tax obligations.